EFL teacher blended professional training: a review of learners’ online and traditional learning interactions quality - Arifani, Yudhi; Sri Suryanti; Wicaksono, Bayu Hendro; Nina Inayati; Setiawan, Slamet (Penerbit Universiti Kebangsaan Malaysia, 2020)
An increasing number of researchers have adopted blended learning approaches for the purpose of EFL teachers’ professional development. Current empirical study has been sparse regarding the investigation of interaction quality. This study attempts to address those weaknesses, with the objectives of systematically identifying the quality of interactions in both blended and traditional contexts. A sample of 1000 EFL students from various secondary schools at a provincial level was randomly assigned to rate 120 EFL teachers who attend a year blended professional training program using an online (OLIQ) and traditional (TLIQ) learning interaction quality scales to draw the perceived interaction qualities. After distributing the questionnaires, the data were analysed by applying structural equation modelling (SEM). The findings indicated that the one-year blended teacher professional development program showed a significant influence on their traditional and online teaching interaction qualities. Student-Content (SC) dimension became the highest marker of interaction quality in online instruction settings, while Emotional Support (ES) became the highest marker of interaction quality in the traditional face-to-face instruction settings. Some practical recommendations in light of the findings are offered, such as in terms of online material development and online feedback and assessment.